Fmoc-Diphenylalanine Hydrogels: Optimization of Preparation Methods and Structural Insights - Carlo Diaferia; Elisabetta Rosa; Giancarlo Morelli; Antonella Accardo (MDPI AG, 2022)
Hydrogels (HGs) are tri-dimensional materials with a non-Newtonian flow behaviour formed by networks able to encapsulate high amounts of water or other biological fluids. They can be prepared using both synthetic or natural polymers and their mechanical and functional properties may change according to the preparation method, the solvent, the pH, and to others experimental parameters. Recently, many short and ultra-short peptides have been investigated as building blocks for the formulation of biocompatible hydrogels suitable for different biomedical applications. Due to its simplicity and capability to gel in physiological conditions, Fmoc-FF dipeptide is one of the most studied peptide hydrogelators. Although its identification dates to 15 ago, its behaviour is currently studied because of the observation that the final material obtained is deeply dependent on the preparation method. To collect information about their formulation, here are reported some different strategies adopted until now for the Fmoc-FF HG preparation, noting the changes in the structural arrangement and behaviour in terms of stiffness, matrix porosity, and stability induced by the different formulation strategy on the final material.